Psychopathological predictors of compliance and outcome in weight-loss obesity treatment - De Panfilis, C.; Cero, S.; Dall'Aglio, et al., E. (Acta Biomedica Atenei Parmensis, 2007)
Background: To detect pre-treatment psychopathological predictors of compliance and outcome in a behavioural weight-loss program for obesity. Methods: 68 consecutive obese outpatients were evaluated on a wide range of psychopathological variables before entering a behavioural weight reduction program. Baseline assessment included detection of psychiatric (Axis I) and personality (Axis II) disorders, anxiety and depression levels, temperament and character patterns, alexithymia, and eating attitudes. These variables were then tested as predictors of compliance and weight loss after eight months of active treatment. Results: Baseline presence of Axis I diagnoses was found to enhance the likelihood of good compliance to treatment but to lower probability of good outcome. Different psychopathological (and specifically personality) predictors of outcome were found among patients with and without psychiatric disorders. Conclusions: These data suggest the need to perform a full psychiatric evaluation, including personality assessment, to implement obesity treatment strategies.